FREQUENCY OF HEPATITIS B AND C IN SURGICAL PATIENTS: Hepatitis B and C in Surgical Patients - Ahmed, Brig Zubair; Naqvi, Ali (Pakistan Armed Forces Medical Journal, 2012)
Objectives: To determine frequency of hepatitis B and C in surgical patients Study Design: Cross-sectional survey. Duration: 1st April to 1st Nov 2009. Setting: Combined Military Hospital, Lahore; tertiary care, 1000 bedded hospital. Methods: All patients prepared and admitted for elective surgery were included in the study. Sampling technique was purposive non-probability. Testing of venous blood was done for HBsAg and Anti HCV antibody using 3rd generation ELISA for HCV and indirect ELISA for HBV in the preoperative period. Results: A total of 850 patients undergoing surgery were studied. Mean age of the study population was 41.7±13.7 years. Out of the study population 481(56.5%) were male and 369 (43.5%) were females. Two hundred and eighty eight (33.9%) patients were from urban background and 562 (66.1%) were from rural areas. There were 79 (9.3%) patients found positive for HCV, 37(4.3%) for HBV and 12 (1.4%) patients were found to have both HBV and HCV infections. Conclusion: There is very high frequency of Hepatitis B and C in surgical patients. We recommend mandatory screening of all patients undergoing elective surgery.